Malignancy rates in thyroid nodules classified as Bethesda categories III and IV; a subcontinent perspective - Adnan Zahid; Waqas Shafiq; Khawaja Shehryar Nasir; Asif Loya; Syed Abbas Raza; Sara Sohail; Umal Azmat (Journal of Clinical & Translational Endocrinology, 2021)
Background: Bethesda category III and IV thyroid nodules fall in the indeterminate risk of malignancy category. These nodules have been a relatively elusive entity to manage as previous studies have shown a wide variation in malignancy rates in different regions and institutions across the world. However, data from the subcontinent with regards to this is scarce. Aim and objective: This study aimed to determine the characteristics and malignancy rates of cytology proven Bethesda Category III and IV thyroid nodules and its association with clinical, histopathological and laboratory variables, in the regional population. Method: A retrospective search was performed on all patients with thyroid nodules who presented to this hospital, from January 2011 to September 2018. Patients who had cytology proven Bethesda category III and IV thyroid nodules that underwent surgery were included in the study. Results: Malignancy in Bethesda Category III and Bethesda Category IV thyroid nodules was 29.6% and 47.1%, respectively. There was no significant association determined between malignancy rate and various clinical, histopathological, and radiological characteristics. Conclusion: The malignancy rates in Bethesda category III and IV thyroid nodules in this study are significantly higher than that initially suggested by the Bethesda consensus publication but is comparable to international data present.